Step-by-step explanation:
72/64=x/8
=> x = (72×8)/64
=> x = 9.
hope this helps you.
Answer:
x = -2
y=-3
(-2,-3)
Step-by-step explanation:
Both equations are equal to y
We can set them equal to each other
y = 3x + 3
y = x − 1
3x+3 = x-1
Subtract x from each side
3x+3 -x = x-1-x
2x+3 = -1
Subtract 3 from each side
2x+3-3 = -1-3
2x = -4
Divide each side by 2
2x/2 = -4/2
x = -2
Now we need to find y
y = x-1
y = -2-1
y = -3
y = x-1
Answer:
1st one, x=-1
2nd on, y=2
Step-by-step explanation:
Answer:
No
Step-by-step explanation:
When you square a number, you chose a number and multiplying itself. If you did the square root of 25, you would get 5. However if you divided 25 by 2, you would get 12.5 which is NOT the square root.